A Simplified Design of CPAP Device Construction by Using Arduino NANO for OSA Patients - Hadeel K. Aljobouri , Athra’a sabeeh Mikha, (Design Engineering, 2021)
Obstructive sleep apnea (OSA) became more common, particularly in the context of the obesity epidemic. It is linked to serious social, health, and economic consequences. Continuous positive airway pressure (CPAP) is the gold standard of care for mild to extreme OSA patients. Due to the complicated design of the classical CPAP devices that uses complex combination of multi-components, a simplified design is proposed in this paper. As a result of the design complexity that employed a convoluted construction, in this paper, the Arduino Nano board is used instead of the classical microcontroller board. CPAP’s hardware design involves mechanical and electrical components. The hardware system of the electrical model whose main components are the Arduino Nano board, blower, pressure sensor, and Brushless DC (BLDC) motor starts with setup the Integrated Development Environment (IDE) programming according to CPAP criteria of this Nano board. Later, the Proportional-Integral-Derivative (PID) controller’s library was used to control the motor speed and pressure set value. PID controller library has achieved the best results as it obtains the motor speed with the breathing event for helping the patients mitigate their abnormal breathing pattern through increased motor speed in inhalation and decreased it in exhalation time. It also helped to minimize circuit’s construction (PID circuit) by using this library via IDE. This controller is important in the CPAP device to ensure the safety of this device for treating the patients. The safety is achieved via the increment of the pressure at the inhalation event and decrease it at the exhalation event in order to treat the OSA patients.